Servicing the Cummins PT(G) fuel pump [filem jalur] (Tarrytown, NY : Prentice-Hall Media, 1982)
1. Fuel pump : diasassembly -- 2. The shut-down valve and pulsation damper -- 3. Gear pump : overhaul -- 4. Front drive cover : disassembly -- 5. Front drive cover : assembly -- 6. Fuel pump : assembly